Improving concussion education: consensus from the NCAA-Department of Defense Mind Matters Research & Education Grand Challenge. Issue 22 (10th September 2020) - Kroshus, Emily; Cameron, Kenneth L; Coatsworth, J Douglas; D'Lauro, Christopher; Kim, Eungjae; Lee, Katherine; Register-Mihalik, Johna K; Milroy, Jeffery J; Roetert, E Paul; Schmidt, Julianne D; Silverman, Ross D; Warmath, Dee; et al.
Abstract : Early disclosure of possible concussive symptoms has the potential to improve concussion-related clinical outcomes. The objective of the present consensus process was to provide useful and feasible recommendations for collegiate athletic departments and military service academy leaders about how to increase concussion symptom disclosure in their setting. Consensus was obtained using a modified Delphi process. Participants in the consensus process were grant awardees from the National Collegiate Athletic Association and Department of Defense Mind Matters Research & Education Grand Challenge and a multidisciplinary group of stakeholders from collegiate athletics and military service academies. The process included a combination of in-person meetings and anonymous online voting on iteratively modified recommendations for approaches to improve concussion symptom disclosure. Recommendations were rated in terms of their utility and feasibility in collegiate athletic and military service academy settings with a priori thresholds for retaining, discarding and revising statements. A total of 17 recommendations met thresholds for utility and feasibility and are grouped for discussion in five domains: (1) content of concussion education for athletes and military service academy cadets, (2) dissemination and implementation of concussion education for athletes and military service academy cadets, (3) other stakeholder concussion education, (4) team and unit-level processes and (5) organisational processes. Collectively, these recommendations provide a path forward for athletics departments and military service academies in terms of the behavioural health supports and institutional processes that are needed to increase early and honest disclosure of concussion symptoms and ultimately to improve clinical care outcomes.